Allergen immunotherapy for allergic asthma: The future seems bright. (April 2023) - Diamant, Zuzana; van Maaren, Maurits; Muraro, Antonella; Jesenak, Milos; Striz, Ilja
Abstract: Allergen specific immunotherapy (AIT) is the only causal therapeutic option for allergic airway diseases including asthma and allergic rhinitis. AIT has been shown to restore the allergen immune tolerance, can modify both the early and late-onset allergen-specific airway hyperreactivity, helps to achieve disease control/remission and prevents new sensitisations. Recent real life data on long-term effectiveness of house dust mite (HDM) AIT in a large group of patients with HDM-driven asthma further underscored its unique therapeutic potential as well as confirmed previous data with pollen AIT. More widespread use of this causal treatment in select patient populations should further move this promising therapeutic field. In this mini-review, we discuss updates on new insights based on real world patient data. Highlights: Allergen immunotherapy (AIT) is the only causal treatment of allergic diseases including asthma which also has a proven cost-effectiveness. The key benefits of AIT consist of disease modifying effects and protective (preventive) properties against the allergic march. Real-life data show long-term effectiveness (disease remission/modification) of HDM-AIT in HDM-driven asthma across 10 years follow-up. Clinical benefits have also been achieved with pollen allergen extracts (both SCIT and SLIT), but more long-term real-life data in larger cohorts should confirm the persistence of clinical effectiveness in asthma. Predictive biomarkers identifying responders to AIT represent an unmet need while research is ongoing.